Understanding political ideas and movements - Harrison, Kevin (Manchester University Press, 2003)
Written specifically to cover the A2 component of the GCE Government and Politics A-level, this book is a comprehensive introduction to the political ideas and movements that have shaped the modern world. Underpinned by the work of major thinkers such as Hobbes, Locke, Marx, Mill, Weber and others, the first half of the book looks at political concepts including the state and sovereignty, the nation, democracy, representation and legitimacy, freedom, equality and rights, obligation and citizenship. There is also a specific chapter which addresses the role of ideology in the shaping of politics and society. The second half of the book addresses traditional theoretical subjects such as socialism, Marxism and nationalism, before moving on to more contemporary movements such as environmentalism, ecologism and feminism. The subject is covered in a clear, accessible style, and includes a number of student-friendly features, such as chapter summaries, key points to consider, definitions and tips for further sources of information. There is a definite need for a text of this kind. It will be invaluable for students of government and politics at introductory level.